Quantum non-demolition measurement in the interferometer - Khokhlov, Dmitri (International Journal of Physical Research, 2020)
The schemes of the arrangements based on the Mach-Zehnder interferometer and the interferometer with two polarizing beam splitters are considered. The interferometers in both the schemes are equipped with some devices, creating a Kerr medium, to perform the quantum non-demolition measurement of a single photon. Such a device gives which way information of the photon while preserving the work of the interferometer.